Experiences of Black Alumnae from PWIs: Did they Thrive?. Issue 2 (4th May 2017) - Kelly, Bridget Turner; Segoshi, Megan; Adams, Lauren; Raines, Alyscia
Abstract : This study qualitatively examines 16 Black alumnae's college experiences from a Black feminist thought intersectional lens. Findings reveal they graduated but did not thrive in the ways described by the thriving quotient and point to ways institutions can measure success not by graduation alone but by all students leaving college with wholeness, well-being, and self-efficacy.